2022
DOI: 10.4174/astr.2022.103.2.72
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative lymphocyte-to-C-reactive protein ratio predicts hepatocellular carcinoma recurrence after surgery

Abstract: Purpose This study was performed to determine the prognostic value of lymphocyte-to-CRP ratio after curative resection for hepatocellular carcinoma. Methods Between July 2010 and October 2021, 173 consecutive patients (144 male, 29 female) who underwent surgical resection for pathologically confirmed hepatocellular carcinoma were included in this retrospective study. Cox regression analysis was used to evaluate the relationship between clinicopathological characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…However, 11 were not suitable for inclusion criteria. Finally, we identi ed 31 studies from 29 articles published between 2020 and 2023 [14,15,16,17,18,19,20,21,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44]. The ow diagram of the literature search was shown in Fig.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, 11 were not suitable for inclusion criteria. Finally, we identi ed 31 studies from 29 articles published between 2020 and 2023 [14,15,16,17,18,19,20,21,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44]. The ow diagram of the literature search was shown in Fig.…”
Section: Search Resultsmentioning
confidence: 99%
“…Subsequently, its prognostic value was also con rmed in liver, pancreatic and breast cancer [20,26,41]. C-reactive protein as a type of acute protein induced by liver cell, can re ect the in ammatory response in a timely and effective manner [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 35 , 36 In terms of HCC, high LCR was found to be a predictor for better overall survival, as well as recurrence-free survival after liver resection. 37 Recently, Lo et al found that pre-treatment NLR could be a valuable marker to predict the survival and hepatotoxicity in HCC patients treated with stereotactic ablative radiation therapy (SART). 34 However, no related study about the relationship between LCR and radiotherapy for HCC has been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…The association between chronic inflammation and cancer development and progression is well-established, encompassing cellular transformation, promotion, survival, proliferation, invasion, angiogenesis, and metastasis [ 4 6 ]. Notably, elevated circulating levels of CRP, indicative of inflammatory status, have been linked to poor prognoses in various cancers, including endometrial, liver, cervical, colorectal, breast, and non-small cell lung cancer [ 7 8 9 ].…”
Section: Introductionmentioning
confidence: 99%